2011
DOI: 10.1177/1470320310387177
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of renin-angiotensin system genes as a risk factor for high-altitude pulmonary oedema

Abstract: The genes of the renin--angiotensin system (RAS) play an important role in the regulation of pulmonary vascular tone. Although studies on individual genes polymorphisms have reported association with high-altitude pulmonary oedema (HAPE), studies on multiple genes or epistasis are lacking. We therefore investigated the association of the RAS polymorphisms with HAPE. In a case-control design, we screened 163 HAPE-resistant/controls (HAPE-r) and 160 HAPEpatients (HAPE-p) of Indian origin for eight polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
(49 reference statements)
0
18
1
Order By: Relevance
“…Several previous studies have assessed the association between HAPE susceptibility and the ACE I/D (rs4340) polymorphism, but the results have been inconsistent (Kumar et al 2004;Hotta et al 2004;Stobdan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have assessed the association between HAPE susceptibility and the ACE I/D (rs4340) polymorphism, but the results have been inconsistent (Kumar et al 2004;Hotta et al 2004;Stobdan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The I/D polymorphism is an Alu repeat located in intron 16 and has been associated with a wide spectrum of disease phenotypes, including HAPE (Charu et al 2006;Stobdan et al 2011). The A240T SNP is located in the promoter region −240 bp from the initiation codon (Qi et al 2008).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…Although genetic variation provides a possible mechanism to explain inter-individual differences in performance in response to hypoxia/susceptibility to HAPE and a significant association has been identified in the polymorphic variants of these genes and occurrence/sensitivity to HAPE, however, the definite role of these SNPs has yet to be established. Some recent studies have shown a possible association between the polymorphisms existing in the genes of the RAAS pathway (rennin-angiotensin-aldosterone system) playing a key role in regulation of vascular tone circulatory homeostasis) and sensitivity of an individual to develop HAPE 52,53) . Hypoxia-inducible factor-1 (HIF-1) is a basic transcription factor that is involved in many important homeostatic responses to hypoxia.…”
Section: Genetic Risk Factors For Hapementioning
confidence: 99%
“…For example, Dehnert et al [16] studied 20 controls and 19 cases of HAPE patients and found that the ACE insertion or deletion polymorphism had no association with susceptibility to HAPE among the mountaineer population. However, another study examined 163 controls and 160 cases of HAPE patients and found that the allele frequencies were significantly different in the Indian population (p < 0.05) [17]. Although genotypes of ACE associated with HAPE susceptibility have been reported, the results have not been consistent.…”
Section: Raas Pathway Genementioning
confidence: 99%
“…They found that the high frequency wild-type –344T allele was positively associated with adaptation to high altitude. Stobdan et al [17 ]screened 163 controls and 160 HAPE patients from Indian descent for eight polymorphisms of four RAAS genes (ACE, Ang, AngR1 and AngR2) in a case-control study. Significant difference in genotype and allele frequencies of the ACE I/D and AGT M235T polymorphisms were observed between the two groups.…”
Section: Raas Pathway Genementioning
confidence: 99%